2018
DOI: 10.29252/jrh.8.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between treatment motivation, substance use, craving, withdrawal symptoms and health locus of control in addicted patients

Abstract: Increasing tendency to drug use is a major social problem, Treatment attempts, regardless of the motivation, are not complete. The study aimed to investigate the relationship between treatment motivation, substance use, craving, withdrawal symptoms and health locus of control in addicted patients. Research population this study included all male and female patients referring to the addiction treatment center. The convenience sampling was used to select the sample and the sample size was determined as 100 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The difference between self-esteem scores before and after the intervention was significant, indicating that this study’s empowering education significantly improved the self-esteem of adolescents. According to research by Moshki [ 51 ], teaching people life skills improves their abilities (such as problem-solving, assertiveness, controlling anger, etc.) and gives them the power to put their knowledge, attitudes, and values into practice, leading to more positive motivation and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between self-esteem scores before and after the intervention was significant, indicating that this study’s empowering education significantly improved the self-esteem of adolescents. According to research by Moshki [ 51 ], teaching people life skills improves their abilities (such as problem-solving, assertiveness, controlling anger, etc.) and gives them the power to put their knowledge, attitudes, and values into practice, leading to more positive motivation and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Yang menentukan merokok tidaknya seseorang adalah adanya keyakinan dalam dirinya untuk mengantisipasi resiko akibat rokok. Keyakinan ini terbentuk dari faktor internal (pengalaman dan kemantapan diri) maupun faktor eksternal (campur tangan Tuhan, perilaku tenaga kesehatan atau akses terhadap layanan kesehatan) (M. Moshki, M. Panahi-Shahri, F. Najarpour, and M. Mirzania, 2018). Sumber internal-eksternal ini saling mempengaruhi satu sama lain, sehingga kadang dalam budaya Nusantara (Jawa khususnya) tidak dapat dibedakan secara jelas mana pengaruh internal, mana pengaruh eksternal.…”
Section: F Diskusi Gap Antara Pengetahuan Dan Sikap Terhadap Rokokunclassified
“…In Iran, the number of drug users is estimated to be approximately 1.8 to 3.3 million people, of which opioids are the most consumed. 3 As most treatment and rehabilitation interventions for addicts have failed, and in many cases, the person has reused these drugs and substances due to psychological dependence, it seems to prevent exposure or the tendency of young people to abuse. Materials are the most effective way to prevent the occurrence and increase the prevalence of addiction in society.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, interventions that emphasize the modification and management of emotion regulation strategies can play an important role in prevention, treatment, prevention of relapse, and temptation. 3 In a study, Franques et al, 17 identified emotion innovation (one of the components of emotion regulation) as a predisposing factor for substance abuse. In the Aldao and Nolen-Hoeksema study titled Characteristics of cognitive emotion regulation strategies, the results showed: the relationship between emotion regulation dysfunction and alcohol abuse and eating disorders is moderated by reward sensitivity.…”
Section: Introductionmentioning
confidence: 99%